1994
DOI: 10.1016/0014-5793(94)00747-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate carboxykinase of Trypanosoma brucei is targeted to the glycosomes by a C‐terminal sequence

Abstract: Import of proteins into the glycosomes of 7Y brucei resembles the peroxisomal protein import in that C-terminal SKL-like tripeptide sequences can function as targeting signals. Many of the glycosomal proteins do not, however, possess such C-terminal tripeptide signals. Among these, phosphoenolpyruvate carboxykinase (PEPCK (ATP)) was thought to be targeted to the glycosomes by an N-terminal or an internal targeting signal. A limited similarity to the N-terminal targeting signal of rat peroxisomal thiolase exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
(19 reference statements)
0
6
1
Order By: Relevance
“…In cells expressing CAT without signal (pJP44) very little enzyme was detected in the glycosomes, whereas in the positive control (cells expressing CAT containing a PTS-1 (pJP62)) over 80% of the CAT activity was associated with the glycosomes. In contradiction to a recent report [26], in cells expressing the thiolase-CAT fusion proteins approximately 70-80% of the enzyme activity was associated with the glycosomes (pHD443, pHD448). In fact, the results for glycosomal import of thiolase fusion proteins paralleled those observed for peroxisomal import of the same proteins in mammalian cells [10].…”
Section: Function Of the Pts-2 In Glycosomal Targetingcontrasting
confidence: 97%
“…In cells expressing CAT without signal (pJP44) very little enzyme was detected in the glycosomes, whereas in the positive control (cells expressing CAT containing a PTS-1 (pJP62)) over 80% of the CAT activity was associated with the glycosomes. In contradiction to a recent report [26], in cells expressing the thiolase-CAT fusion proteins approximately 70-80% of the enzyme activity was associated with the glycosomes (pHD443, pHD448). In fact, the results for glycosomal import of thiolase fusion proteins paralleled those observed for peroxisomal import of the same proteins in mammalian cells [10].…”
Section: Function Of the Pts-2 In Glycosomal Targetingcontrasting
confidence: 97%
“…We therefore decided to repeat such an analysis in S. cerevisiae, using a peroxisomal protein of S. cerevisiae as reporter. Because it has been demonstrated for some PTS1-containing enzymes that deletion of the PTS1 does not block import into peroxisomes (23,26,27), we first demonstrated that import of MDH3 is completely dependent upon the presence of its PTS1 and the PTS1 receptor, Pex5p. Furthermore, we showed that this protein could be epitope-tagged without any noticeable effect on its import efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Because some PTS1-containing proteins contain additional (internal) peroxisomal targeting signals (23,26,27), we tested whether import of MDH3 completely relies on this tripeptide. To this purpose we made one PTS1 mutant from which the last two amino acids were deleted (MDH3⌬KL) and one PTS1 mutant in which the positively charged lysine residue was replaced by the negatively charged glutamic acid residue (MDH3-SEL).…”
Section: Mdh3mentioning
confidence: 99%
“…This yielded plasmid pXB-L, which encodes a fusion protein consisting of Ble-Cys-Ala-Ser-Leu-Ile-Luc. pXB-L⌬SKL was constructed in the same way, by subcloning the BLE gene PCR product upstream and in frame with the LUC gene in pLUH207 (48), which encodes a Luc lacking the SKL targeting signal. The targeted and untargeted BLE-LUC genes were excised from their respective plasmids on StuI-BamHI fragments and subcloned into pX digested with SmaI and BamHI to yield pXB-L. Sequencing of the BLE-LUC junction confirmed that the two coding regions were joined in frame.…”
Section: Methodsmentioning
confidence: 99%
“…However, mutational analysis has established that considerably more variation in the signal is tolerated for efficient glycosomal targeting in Trypanosoma brucei than for peroxisomal targeting (47). Several glycosomal proteins contain an SKL sequence, or one closely related to it, at their carboxy termini (46), and some of these have been demonstrated to function in glycosomal targeting (7,48,49). The functional relationship of type 2 targeting signals is less clear, as there are conflicting reports as to whether the type 2 peroxisomal targeting signal is capable of directing proteins to the glycosome (6,49).…”
mentioning
confidence: 99%